A modern perspective of Islamic economics and finance - Gundogdu, Ahmet Suayb (Emerald Publishing Limited, 2019)
Traditionally, academic reflections on Islamic economics and finance have relied on a misleading understanding of Maqasid Al-Shari'ah. Much of the current research on the subject dogmatically adheres to the teachings of classical Islamic philosophers and does not appeal to practitioners of economics and finance who are looking for guidance on practical application rather than academic verbosity.This book aims to develop a blueprint for Islamic economics and finance by starting at the grass roots of trade and commerce. The majority of the world population, both in developed countries and emerging markets, have serious concerns over financial sustainability for themselves or their children. Islamic finance is meant to support an economy through genuine transactions and fulfil a duty to achieve a fair and prosperous society. Unfortunately, the industry has failed to fulfil this proposition and converged to conventional systems that do not link to the wider economic priorities of Islam. This book positions Islamic finance within the economic priorities of Islam while providing a cohesive understanding of Islamic economics and finance in a clear and practical manner. In doing so, the book provides the to-dos and not-to-dos of Islamic economics and finance, and instigates an Islamic monetary system in which people, not central banks, create money as long as they produce things demanded by other people.
Keywords: Banks and banking -- Religious aspects -- Islam.; Finance -- Religious aspects.; Business & Economics -- General.; Economics, finance, business & management.; elektronické knihy; electronic books